2022
DOI: 10.1177/00220027221100254
|View full text |Cite
|
Sign up to set email alerts
|

Under the Umbrella: Nuclear Crises, Extended Deterrence, and Public Opinion

Abstract: How robust is public support for extended nuclear deterrence in patron and client states? Recent studies have improved scholarly understanding of US public opinion about nuclear weapon use against non-nuclear adversaries. Yet, there is limited knowledge of public attitudes regarding retaliation for nuclear strikes against US allies. We develop a theoretical typology of nuclear crises and investigate this phenomenon with a novel survey experiment ( n = 6,623). Americans, Japanese, and South Koreans viewed reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 48 publications
1
4
0
1
Order By: Relevance
“…As argued by Snyder and Borghard (2011), the latter is an important distinction for the audience costs theory, yet has rarely been tested in audience costs experiments. Our finding that the US public preference regarding nuclear use remains constant irrespective of leaders' threats also adds to the recent wave of "nuclear taboo" experiments (Allison, Herzog, and Ko 2022;Bowen, Goldfien, and Graham 2023;Dill, Sagan, and Valentino 2022;Horschig 2022;Koch and Wells 2021;Press, Sagan, and Valentino 2013;Rathbun and Stein 2020;Sagan and Valentino 2017;Smetana and Vranka 2021;Smetana and Onderco 2023;Sukin 2020).…”
Section: Discussionsupporting
confidence: 52%
“…As argued by Snyder and Borghard (2011), the latter is an important distinction for the audience costs theory, yet has rarely been tested in audience costs experiments. Our finding that the US public preference regarding nuclear use remains constant irrespective of leaders' threats also adds to the recent wave of "nuclear taboo" experiments (Allison, Herzog, and Ko 2022;Bowen, Goldfien, and Graham 2023;Dill, Sagan, and Valentino 2022;Horschig 2022;Koch and Wells 2021;Press, Sagan, and Valentino 2013;Rathbun and Stein 2020;Sagan and Valentino 2017;Smetana and Vranka 2021;Smetana and Onderco 2023;Sukin 2020).…”
Section: Discussionsupporting
confidence: 52%
“…Their findings demonstrated that American citizens were significantly less averse to the military use of nuclear weapons than previously thought, setting off a new wave of research into the nuclear nonuse norm, or the “nuclear taboo.” Unlike earlier historical accounts of high-level decision-making (Tannenwald 2007; Paul 2009; Sauer 2015), this new wave has been fielding large-N surveys to examine public attitudes toward the use of nuclear weapons under different experimental conditions (Sagan and Valentino 2017; Haworth, Sagan, and Valentino 2019; Rathbun and Stein 2020; Koch and Wells 2020; Montgomery and Carpenter 2020; Smetana and Vranka 2021; Bowen, Goldfien, and Graham 2022; see Smetana and Wunderlich 2021 for a review). However, most of these studies have mainly focused on the United States; only recently have scholars started to conduct these experiments to investigate (non)use attitudes in other nuclear-armed countries (Sukin 2020; Egel and Hines 2021; Dill, Sagan, and Valentino 2022; Horschig 2022; Allison, Herzog, and Ko 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, such moral concerns remain salient even when issues of state and international security are at stake, that is, when the country in question is developing nuclear weapon capabilities (Tomz and Weeks 2020). A recent survey experimental study likewise indicates that even in a hypothetical scenario in which North Korea launches a nuclear attack, a clear majority of U.S., Japanese, and South Korean publics reject nuclear retaliation, a decision that is driven at least in part by concern about civilian casualties in North Korea (Allison, Herzog, and Ko 2022). These findings are a strong indicator that human rights violations and the targeting of civilians are important factors that shape public opinion toward states and societies affected by war, in both Western and non-Western democracies.…”
Section: Public Opinion On Conflict Violence and Gendermentioning
confidence: 99%